Assessment Of Knowledge Management Maturity In An R&D Organization - Kuriakose, K.K.; Raj, Baldev; Malathi, R.; Parameswaran, V.; Murty, S.A.V. Satya (Journal of Knowledge Management Practice, 2011)
Assessment Knowledge Management Maturity is a necessary step for any organization which has initiated the journey of Knowledge Management. Also validation of any knowledge management maturity model is an important test for the model. This paper details the work done to achieve the dual purpose of assessing the knowledge management maturity of an R&D organization and validating the Knowledge Management Maturity Model developed by the authors.
Keywords: Knowledge management; Maturity assessment; Maturity model validation